1996
DOI: 10.1007/bf01092520
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and nutritional potential of yam bean seeds (Pachyrhizus erosus L. Urban)

Abstract: Pachyrhizus erosus seeds were analysed for proximate composition, minerals, protein fractions, antinutritional factors, and rotenoids. The seeds showed a high content of proteins, lipids, Fe and Ca, in comparison to other legumes. Glutelins constitute the highest protein fraction, followed by globulins. Antinutritional substances detected as tannins, hemagglutinating activity and trypsin inhibitory activity, were in low concentrations. Seeds were also processed to obtain a flour which showed proper characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
4
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 12 publications
4
25
4
1
Order By: Relevance
“…The results also showed that yam bean seed protein was different from that of other legumes such as soy bean (Vasconcelos et al, 2010), peas, common bean (Chan & Phillips, 1994;Morales et al, 2001) and mucuna seeds (Sridhar & Bhat, 2007) that have globulin as the dominant fraction. Santos et al (1996) reported glutelin as the most dominant protein fraction in yam bean seed protein (P. erosus) with globulins, albumins and prolamins reported at 28.8, 16.3 and 7.0%, respectively, contrary to the results of this study. This disparity may be due to the differences in soil fertility and climatic conditions where the crops were grown.…”
Section: Fractionation Of Yam Bean (P Erosus) Seed Proteincontrasting
confidence: 99%
See 4 more Smart Citations
“…The results also showed that yam bean seed protein was different from that of other legumes such as soy bean (Vasconcelos et al, 2010), peas, common bean (Chan & Phillips, 1994;Morales et al, 2001) and mucuna seeds (Sridhar & Bhat, 2007) that have globulin as the dominant fraction. Santos et al (1996) reported glutelin as the most dominant protein fraction in yam bean seed protein (P. erosus) with globulins, albumins and prolamins reported at 28.8, 16.3 and 7.0%, respectively, contrary to the results of this study. This disparity may be due to the differences in soil fertility and climatic conditions where the crops were grown.…”
Section: Fractionation Of Yam Bean (P Erosus) Seed Proteincontrasting
confidence: 99%
“…Both cooked and raw samples of the two yam bean accessions in this study exhibited considerably high IVPD (Table 3). The protein digestibility values in this study were higher than those reported for P. erosus flour by Santos et al (1996). Yam bean seed flour production by Santos et al (1996) entailed soaking, cooking, drying, milling, defatting and then drying.…”
Section: In-vitro Protein Digestibility (Ivpd)contrasting
confidence: 79%
See 3 more Smart Citations